2021
DOI: 10.21037/jtd-21-915
|View full text |Cite
|
Sign up to set email alerts
|

Long-term radiation therapy-related risk of second primary malignancies in patients with lung cancer

Abstract: Background: With the improvement of cancer therapy, a second primary malignancy (SPM) occurs more commonly among cancer survivors. At present, it remains unclear whether the radiation therapy for the initial lung cancer will increase the risk of developing a SPM. This study aims to investigate the long-term risk of a SPM attributable to the radiation therapy in patients with the initial lung cancer. Methods: Patients initially diagnosed with lung cancer between January 1975 and November 2011 were identified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
0
7
0
2
Order By: Relevance
“…And we found that the risk of second primary gastrointestinal malignancies was increasing after the implementation of radiotherapy. On the other hand, using the data from 1975 to 2011, Han et al have revealed that radiotherapy was considerably related to a low risk of developing SPMs in lung cancer patients, especially second primary prostate cancer and thyroid cancer [ 22 ]. Han et al also showed a significantly increased risk for second primary esophageal carcinoma in lung cancer patients, which was similar to our conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And we found that the risk of second primary gastrointestinal malignancies was increasing after the implementation of radiotherapy. On the other hand, using the data from 1975 to 2011, Han et al have revealed that radiotherapy was considerably related to a low risk of developing SPMs in lung cancer patients, especially second primary prostate cancer and thyroid cancer [ 22 ]. Han et al also showed a significantly increased risk for second primary esophageal carcinoma in lung cancer patients, which was similar to our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with fully resected NSCLC, another study did not advise routine postoperative radiation [ 21 ]. On the other hand, two cohort studies reported that radiotherapy may result in a lower risk of developing SPM, including prostate cancer and thyroid cancer, among lung cancer patients [ 22 ]. However, it has not been sufficiently addressed whether developing SPMs is a severe adverse event following radiotherapy for lung cancer, based on the sparse and contradictory findings of earlier research.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al . performed a population‐based study on long‐term RT‐related risk of developing secondary malignancies in lung cancer patients, and the result showed that higher risk of EC (HR = 1.76, P < 0.001) and lower risk of female breast cancer (HR = 0.65, P = 0.001) were found in primary lung cancer patients with RT after propensity‐score‐matching‐adjusted competing risk regression 17 . However, no risk difference in secondary lung cancer was detected in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies are designed to assess the frequency of multiple primaries in a specific body part such as gynecologic malignancies, and the colorectal or aerodigestive tracts [11][12][13][14][15][16][17]. The reports evaluating the effect of cancer treatment on the development of second primaries demonstrated that both chemotherapy and radiotherapy can cause secondary primaries [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%